Systematic Literatur Review of Productive Waqf in Indonesia and Their Contribution to SDGs: Tinjauan Sistematis Model Wakaf Produktif di Indonesia dan Kontribusinya terhadap SDGs - Sa’adah, Tsuroyya Putri; Ritonga, Iskandar; Latifah, Fitri Nur; Mugiyati, Mugiyati (Perisai : Islamic Banking and Finance Journal, 2025)
The developing waqf management models is still focused on traditional sectors such as agriculture, plantations, and using waqf assets in building and land. This research aims to summarize models of productive waqf management in Indonesia. the method employed in this study is the Systematic Literature Review (SLR). The research questions were formulated using the PICOC criteria, which included population, intervention, comparison, outcomes, and context. As a result, several studies were identified that describe successful models of productive waqf management, which can serve as literacy resources for each nadzir’s waqf institution throughout Indonesia.